A universal strategy for metal oxide anchored and binder-free carbon matrix electrode: A supercapacitor case with superior rate performance and high mass loading. (January 2017) - Zhang, Xuan; Luo, Jiangshui; Tang, Pengyi; Ye, Xiaoliang; Peng, Xinxing; Tang, Haolin; Sun, Shi-Gang; Fransaer, Jan
Abstract: Despite the significant advances in preparing carbon-metal oxide composite electrodes, strategies for seamless interconnecting of these two materials without using binders are still scarce. Herein we design a novel method for in situ synthesis of porous 2D-layered carbon–metal oxide composite electrode. Firstly, 2D-layered Ni-Co mixed metal-organic frameworks (MOFs) are deposited directly on nickel foam by anodic electrodeposition. Subsequent pyrolysis and activation procedure lead to the formation of carbon–metal oxides composite electrodes. Even with an ultrahigh mass loading of 13.4 mg cm −2, the as-prepared electrodes exhibit a superior rate performance of 93% (from 1 to 20 mA cm −2 ), high capacitance (2098 mF cm −2 at a current density of 1 mA cm −2 ), low resistance and excellent cycling stability, making them promising candidates for practical supercapacitor application. As a proof of concept, several MOF derived electrodes with different metal sources have also been prepared successfully via the same route, demonstrating the versatility of the proposed method for the preparation of binder-free carbon–metal oxide composite electrodes for electrochemical devices. Graphical abstract: A novel 2D carbon−metal oxide composite electrode was prepared by four steps and demonstrated as promising binder-free electrode materials for supercapacitors with ultrahigh rate performance of 93% (from 1 to 20 mA cm −2 ) and high mass loading (13.4 mg cm −2 ). Moreover, this new general strategy is also expected to facilitate the synthesis of carbon–metal oxide composite electrodes for other electrochemical devices. Highlights: Facile synthesis of 2D-Co-Ni mixed MOFs by electrodeposition. In-situ growth of metal oxide anchored carbon matrix on Ni foam. The achieved 2D-CMO electrode exhibits excellent rate performance with high mass loading. This approach is expected to be a universal strategy for in-situ growth of metal oxide anchored carbon matrix electrodes.